Restructuring government and the economy - Hyde, A.C
The author describes that the content and nature of public administration depends upon the content and nature of the government it serves. He further explaining the facts that in the last generation the federal government has experienced a sea change: it is itself doing loss but influencing far more. It has at the same time become far more dependent upon institutions outside itself. The author feels that many of us in public administration have kept sufficiently abreast of the problems and implications of the massive changes in American government... The naturen of public management has changed and it must look outward more, inward relatively less. The fact is that in the current climate of political pessimism
Keywords: Government; Public Administration